2012
DOI: 10.1055/s-0032-1307262
|View full text |Cite
|
Sign up to set email alerts
|

Acute Schmorl's Node during Strenuous Monofin Swimming: A Case Report and Review of the Literature

Abstract: Study Design This case report describes an acute Schmorl's node (SN) in an elite monofin athlete during exercise. The patient presented with severe back pain and leg numbness and was managed successfully with conservative treatment. Objective The aim of our communication was to describe a rare presentation of a common pathological condition during an intense sport. Background Swimming is not generally considered to be a sport activity that leads to spinal injuries. SNs are usually asymptomatic lesions, inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Clinically, they are usually believed to be asymptomatic incidental findings on plain radiographs, computed tomography (CT), and MRI and do not require surgical treatment. However, in some cases, they may denote a severe symptomatic process and cause acute low back pain [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, they are usually believed to be asymptomatic incidental findings on plain radiographs, computed tomography (CT), and MRI and do not require surgical treatment. However, in some cases, they may denote a severe symptomatic process and cause acute low back pain [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The histological origins of pain are not yet fully established. It has been postulated that in affected vertebrae there are higher proportions of disc marrow contacts and that the herniating materials irritate a special intravertebral nociceptive system, ultimately generating pain [ 19 , 20 ]. Fields et al [ 20 ] reported a higher nerve density was found in endplate defects than in normal endplates.…”
Section: Discussionmentioning
confidence: 99%
“…A reasonable comparison could be made with what is done in the field of monofin research. The average size of the samples of the 5 most recent papers available on PubMed on monofin swimming (search performed on PubMed using "monofin" as keyword, last consulted December 2, 2016) was of 7.6 ± ± 5.4 [8][9][10][11][12]. Therefore, the sample size of the present study was considered as an acceptable target.…”
Section: Discussionmentioning
confidence: 99%
“…Schmorl’s nodes are intervertebral discs that have herniated into the vertebral body. Schmorl’s nodes are asymptomatic and typically an incidental finding with an incidence as high as 76% and a slightly higher predominance in males [ 1 , 2 ]. They are most commonly located in the thoracolumbar spine [ 1 , 3 - 5 ].…”
Section: Introductionmentioning
confidence: 99%